1996
DOI: 10.1259/0007-1285-69-822-522
|View full text |Cite
|
Sign up to set email alerts
|

Cross-calibration of a fan-beam X-ray densitometer with a pencil-beam system

Abstract: This study describes the cross-calibration of two Hologic bone densitometers, one using a fan-beam X-ray source (QDR4500/A) and the other a pencil-beam source (QDR1000/W). The QDR4500/A allows spine and hip measurements to be made at three principal speeds. Results from two spine phantoms and 154 patients showed no significant difference in the absolute values or precision between speeds. The middle speed (taking 1 min to scan an adult lumbar spine) was used for the comparison between the instruments. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Recent studies have also shown similar differences when pencil-and fan-beam DXA machines from the same manufacturer are compared (Blake et al, 1993;Faulkner et al, 1993;Abrahamsen et al, 1995;Franck et al, 1995;Bouyoucef et al, 1996;Barthe et al, 1997;Ellis & Shypailo, 1998;Ruetsche et al, 2000;Kolta et al, 2000;Tothill et al, 2001).…”
Section: Introductionmentioning
confidence: 73%
“…Recent studies have also shown similar differences when pencil-and fan-beam DXA machines from the same manufacturer are compared (Blake et al, 1993;Faulkner et al, 1993;Abrahamsen et al, 1995;Franck et al, 1995;Bouyoucef et al, 1996;Barthe et al, 1997;Ellis & Shypailo, 1998;Ruetsche et al, 2000;Kolta et al, 2000;Tothill et al, 2001).…”
Section: Introductionmentioning
confidence: 73%
“…In general, close agreement (mean differences of < 1-2%) was seen when the bone mineral density results of the spine, femur, or forearm from the QDR-4500A bone densitometer were compared with those from earlier Hologic models. However, 2 studies showed that the total body BMC measured by the QDR-4500A bone densitometer is 5-6% lower than that observed with the QDR-2000 (26) and QDR-1000 bone densitometers (27).…”
Section: Discussionmentioning
confidence: 93%
“…Intergenerational comparisons have been published for Hologic (10,11) forearm devices. Faulkner et al (12) found that although there was high correlation (r ϳ 0.99) between the Hologic QDR-1000 and Lunar DPX-L at the ultradistal and 1 ⁄3 distal sites, the regression slope was up to 12% different from unity with offsets of 0.07-0.08 g/cm 2 .…”
Section: Introductionmentioning
confidence: 99%